The Effect of Abdominal Stretching, Yoga, and Dysmenorrhea Exercises on Prostaglandin Levels and Pain - Tyas, Eka Suryaning; Hartono, Soetanto; Wahyuni, Endang Sri; Muhammad, Heryanto Nur; Prasetya, Fika Indah; Sasmito, Priyo (PT Inovasi Pratama Internasional, 2023)
Introduction: Dysmenorrhea, or pain during menstruation, affects a high percentage of women of reproductive age. It can disrupt learning activities at school, cause a lack of concentration, and lead to frequent absences, ultimately decreasing the quality of life for young women. The purpose of this study was to analyze the effect of abdominal stretching, yoga, and dysmenorrhea exercises on prostaglandin levels and pain in school-age adolescents. Method: A quasi-experimental study with an experimental laboratory design was used, with pretest and posttest control groups. The sampling technique used was probability sampling with simple random sampling of 32 female students divided into four groups, with three groups receiving abdominal stretching, yoga therapy, and dysmenorrhea exercises, respectively, and one group serving as the control group. Data was analyzed using one-way ANOVA and the Kruskal-Wallis test. Results: The average prostaglandin levels after treatment were highest in the abdominal stretching group at 31.7 pg/mL and lowest in the dysmenorrhea group at 19.0 pg/mL. The difference in prostaglandin levels was highest in the dysmenorrhea exercise group at 42.5 pg/mL and lowest in the control group at 14.4 pg/mL. Most participants who experienced moderate pain before and after the intervention generally complained of mild pain. Conclusion: The study found a significant effect of abdominal stretching therapy, yoga therapy, and dysmenorrhea exercises on prostaglandin levels and pain. Dysmenorrhea exercises were found to be the most effective therapy in reducing prostaglandin levels and dysmenorrhea pain, compared to abdominal stretching and yoga therapy.